Prescriptive Appropriateness: Inhospital Adherence to Proton Pump Inhibitors Deprescription Flow Chart - Giammarco Baiardi; Giulia Calvini; Serena Panarello; Chiara Fioravanti; Manuela Stella; Antonietta Martelli; Giancarlo Antonucci; Francesca Mattioli (MDPI AG, 2023)
The prescriptive appropriateness of Proton Pump Inhibitors (PPIs) in polypharmacy is controversial. PPIs are often overprescribed and the risk of prescribing errors and adverse drug reactions increases for each additional drug added to therapy. Hence, guided deprescription should be considered and easily implementable in ward practice. This observational prospective study evaluated the implementation of a validated PPIs deprescription flow chart to real-life internal ward activity through the presence of a clinical pharmacologist as an enhancing additional factor by assessment of inhospital prescriber's adherence to the proposed flow chart. Patients' demographics and prescribing trends of PPIs prescriptions were analyzed by descriptive statistics. The final analysis of data included ninety-eight patients (forty-nine male and forty-nine female), aging 75.6 ± 10.6 years; 55.1% of patients had home-PPIs prescriptions, while 44.9% received inhospital-PPIs prescriptions. Evaluation of prescriber's adherence to the flow chart revealed that the percentage of patients with a prescriptive/deprescriptive pathway conforming to that of the flow chart was 70.4%, with low symptomatologic recurrences. The clinical pharmacologists' presence and influence in ward activity may have contributed to this finding, since continuous training of the prescribing physicians is deemed a success-related factor in the deprescribing strategy. Multidisciplinary management of PPIs deprescription protocols shows high adherence by prescribers in real-life hospital settings and low recurrence events.